2016
DOI: 10.1371/journal.pone.0164960
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing the Dynamics of Observed and Simulated Ecosystem Gross Primary Productivity with Time Causal Information Theory Quantifiers

Abstract: Data analysis and model-data comparisons in the environmental sciences require diagnostic measures that quantify time series dynamics and structure, and are robust to noise in observational data. This paper investigates the temporal dynamics of environmental time series using measures quantifying their information content and complexity. The measures are used to classify natural processes on one hand, and to compare models with observations on the other. The present analysis focuses on the global carbon cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 84 publications
0
25
0
Order By: Relevance
“…, ), and in the environmental sciences it has provided insight into model‐data deviations of gross primary productivity to further understand the global carbon cycle (Sippel et al. ). In epidemiology, a recent study on the information‐theoretic limits to forecasting of infectious diseases concluded that, for most diseases, the forecast horizon is often well beyond the time scale of outbreaks, implying that prediction is likely to succeed (Scarpino and Petri ).…”
Section: Discussionmentioning
confidence: 99%
“…, ), and in the environmental sciences it has provided insight into model‐data deviations of gross primary productivity to further understand the global carbon cycle (Sippel et al. ). In epidemiology, a recent study on the information‐theoretic limits to forecasting of infectious diseases concluded that, for most diseases, the forecast horizon is often well beyond the time scale of outbreaks, implying that prediction is likely to succeed (Scarpino and Petri ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, empirical and/or physics-based criteria have been used to constrain snowalbedo feedbacks (Hall and Qu, 2006), constrain carbon cycle projections Wenzel et al, 2014;Mystakidis et al, 2016), or in the context of refining precipitation projections . Moreover, empirical diagnostics are applied to select models for event attribution analyses (Perkins et al, 2007;King et al, 2016;Otto et al, 2015) and analyses of drought projections based on model performance (Van Huijgevoort et al, 2014) or to resample large initialcondition ensembles to alleviate biases without distorting the multivariate structure of climate model output (Sippel et al, 2016b). In the context of land-atmosphere coupling, Fischer et al (2012) and Stegehuis et al (2013) have constrained a re- gional model ensemble over Europe using present-day interannual variability in summer temperature, and observationsbased estimates of summer sensible heat fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Although the full potential of permutation entropy to guide forecasting is not yet realized, many other fields are starting to take advantage of its diagnostic potential. In paleoclimate science, permutation entropy has proven useful for detecting hidden data problems caused by outdated laboratory equipment (Garland et al 2016), and in the environmental sciences it has provided insight into model-data deviations of gross primary productivity to further understand the global carbon cycle (Sippel et al 2016). In epidemiology a recent study on the information-theoretic limits to forecasting of infectious diseases concluded that for most diseases the forecast horizon is often well beyond the time scale of outbreaks, implying prediction is likely to succeed (Scarpino & Petri 2017).…”
Section: Discussionmentioning
confidence: 99%